Analisis Pengaruh Kepuasan Konsumen Terhadap Loyalitas Pembelian Matcha pada Gen Z - Rizqa Aulia Ramadhani; Sekar Ayuningrum; Ruth Natalia Susanti (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of consumer satisfaction on purchase loyalty toward matcha products among Generation Z. The growing interest of Gen Z in matcha is not only driven by trends but also by health-related factors, product quality, and the emotional experience associated with its consumption. This research adopts a descriptive quantitative approach involving 20 participants selected through purposive sampling. Data were collected using an online questionnaire with a Likert scale (1–5), complemented by follow-up interviews with five participants to strengthen the survey findings. The results show that the level of customer satisfaction falls into the “very high” category with an average score of 4.27, while customer loyalty is categorized as “high” with an average score of 3.94. Factors such as product presentation, taste, and accessibility significantly contribute to consumer satisfaction, whereas loyalty is influenced by brand trust, positive consumption experiences, and the willingness to repurchase. These findings affirm that consumer satisfaction plays a crucial role in fostering long-term loyalty toward matcha products among Gen Z.